Superfluid Two-Phase Sound - Putterman, Seth; Heckerman, David; Rosenbaum, Ralph; Williams, Gary (Physical Review Letters, 1979)
The properties of the sound wave propagating in a superfluid two-phase system (liquid helium and its vapor) are investigated. At a frequency sufficiently low so that the superfluid helium and its vapor are in quasistatic equilibrium, there can propagate only one sound mode whose wave-guide-like velocity depends strongly on the vapor properties as well as the velocity of second sound. Near the lambda point, the mode probes the critical properties of the specific heat of the superfluid.